Body Composition and Metabolomics in the Alberta Physical Activity and Breast Cancer Prevention Trial (OR09-02-19). (13th June 2019) - Mcclain, Kathleen; Friedenreich, Christine; Brenner, Darren; Courneya, Kerry; Matthews, Charles; Moore, Steven
Abstract: Objectives: Recent metabolomics studies have identified metabolic correlates of body mass index (BMI), but the degree to which correlations are driven by fat mass as opposed to lean mass has not been established. Our objectives were to 1) replicate findings of BMI-metabolite correlations, and 2) to describe the contributions of FM and LM to the BMI-metabolite associations. Methods: The Alberta Physical Activity and Breast Cancer Prevention Trial was a two-center randomized trial of healthy but inactive, postmenopausal women ( N  = 304). BMI (kg/m 2 ) was calculated using measured weight and height, while whole body dual X-ray absorptiometry estimated fat mass and lean mass. Serum metabolite levels were measured by ultra-performance liquid chromatography and high-resolution/accurate mass spectrometer. We estimated partial Pearson correlations between 1053 metabolites and BMI, adjusting for age, smoking, and study site. Fat mass/m 2 and lean mass/m 2 correlations were estimated similarly, with mutual adjustment for one another to evaluate independent effects after accounting for their positive intercorrelation. Results: Using a Bonferroni-corrected alpha-level <4.75 × 10–5, we observed 39 metabolites correlated with BMI (|r|:0.24–0.42; lowest p-value:7.53 × 10–14), including 25 metabolites that replicate previously-reported associations. Of metabolites correlated with BMI, only 14 were robustly correlated with fat mass/m 2 (|r| > 0.20), and five had virtually no fat mass/m 2 correlation (|r| < 0.10). Six metabolites were more strongly correlated with lean mass/m 2 than with fat mass/m 2 . When we extended the analysis to all metabolites, we found another eight metabolites that were robustly correlated with fat mass/m 2 (|r|:0.24–0.29) and three with lean mass/m 2 (r:0.24–0.27) despite no statistically significant correlation with BMI. Conclusions: BMI may be insufficiently specific, in some cases, for studies of the metabolic effects of adiposity. Many BMI-related metabolites are only weakly correlated with fat mass; some are more directly related to lean mass than fat mass. For those metabolites already being studied in relation to disease risk (e.g., branched chain amino acids), our study demonstrates which aspect of body composition may primarily underlie metabolite-disease associations. Funding Sources: National Institutes of Health Intramural Research Program, Canadian Breast Cancer Research Alliance.